Nilai Pendidikan Agama Hindu Pada Tradisi Mayah Ikut Dalam Upacara Perkawinan Di Desa Pakraman Satra, Kintamani, Bangli - Ida Bagus Putu Eka Suadnyana (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2022)
The Mayah Ikut tradition contains educational values. The strictness of tradition can defeat all global civilizations that want to disturb existing traditions, so symbolic thoughts and ethical actions are characteristic of human dignity that underlies all progress of local culture and society. Cultural acculturation is a custom and its concrete form is the norm. The actions of the local community become customs and traditions, because actions that are successful and profitable tend to be repeated in the same way, over and over again to form. Mayah Ikut has a very deep meaning if it is studied and absorbed, even though it only looks like an offering, but behind it there is something that needs to be revealed to be known together. The values contained in the Mayah Ikut tradition are the value of discipline, the value of togetherness and cultural values